Eclipse (Twilight Saga, ,, 2008)
Description Not Provided

Eclipse (Twilight Saga, ,, 2010)
Bella must choose between her friendship with Jacob and her relationship with Edward as Seattle is ravaged by a mysterious string of killings.

The twilight saga: Breaking dawn, part 1 (Twilight Saga, ,, 2012)
In the highly anticipated fourth installment of the Twilight Saga, a marriage, a honeymoon, and the birth of a child bring unforeseen and shocking developments for Bella and Edward and those they love, including new complications with young werewolf Jacob Black.

Twilight (Twilight Saga, ,, 2009)
Isabella Swan moves to gloomy Forks, Washington to live with her father. She begins her junior year in high school and becomes fascinated by Edward Cullen. He holds a dark secret which is only known by his family. To Edward, Bella is what he has waited 90 years for, a true soul mate. But he knows the further they progress in their relationship the more he is putting Bella and those close to her at risk. Edward tries to warn Bella that she should leave him, but she refuses. A new vampire finds it a challenge to hunt Bella down for her irresistible blood. Now, the game is on and James will not stop until she is killed.

Crepúsculo: un amor peligroso (Alfaguara, 2007)
When seventeen-year-old Bella leaves Phoenix to live with her father in Forks, Washington, she meets an exquisitely handsome boy at school for whom she feels an overwhelming attraction and who she comes to realize is not wholly human.

The twilight saga: New moon (Twilight Saga, ,, 2010)
Bella is still very much in love with Edward. The rest of the vampire coven who call themselves the Cullens, especially Alice, decide to throw Bella a private party for her eighteenth birthday. Things go wrong when Bella cuts her finger and thirst overcomes the vampires. As a result of the danger Bella was put through, the Cullen family decide to leave Forks, Washington. Bella becomes so depressed that she exempts herself from all social activities. But, she realizes she can coexist with childhood friend, Jacob. As usual for Bella, things aren't what they seem. Something is happening to Jacob that he can't explain to Bella, and their friendship starts to deteriorate. But when Alice returns to tell her that Edward thinks she is dead, Bella must go on a journey to save Edward from wanting to die himself.

Twilight zone: the movie (Warner Home Video, 2007)
Four separate stories that take place in a mysterious fifth dimension of imagination.

Tenet (Warner Bros. Home Entertainment, 2020)
Armed with only one word and fighting for the survival of the entire world, the Protagonist journeys through a twilight world of international espionage on a mission that will unfold in something beyond real-time.

Tenet (Warner Bros. Home Entertainment, 2020)
"Armed with only one word -- Tenet -- and fighting for the survival of the entire world, the Protagonist journeys through a twilight world of international espionage on a mission that will unfold in something beyond real time"--Container.

Penelope (Summit Entertainment, 2008)
Penelope Wilhern is born to wealthy socialites. She is afflicted by the Wilhern spell that can only be broken when she finds love. Hidden away in her family's estate, the lonely girl meets a string of suitors in her parent's futile attempt to break the curse. Each eligible bachelor is enamored with Penelope and her sizable dowry, but only until her curse is revealed. Lemon, a mischievous and eager tabloid reporter, wants a photograph of the mysterious Penelope and hires Max to pose as a prospective suitor to get the shot. The handsome down-on-his luck gambler finds himself falling for Penelope. He decides to disappear so he will not disappoint her or to expose his surreptitious ways. Fed up by this latest betrayal and determined to live life on her own terms, Penelope breaks free from her family and ventures into the world alone. She finds adventure and meets Annie, her first friend, and becomes the person she was meant to be.

NCIS: Naval Criminal Investigative Service: The complete second season (Paramount Pictures, 2006)
Led by Special Agent Leroy Jethro Gibbs, this squad of highly trained N.C.I.S. agents proves it is willing to make the ultimate sacrifice to thwart espionage and terrorism around the world.
Disc 1: See no evil ; The good wives club ; Vanished ; Lt. Jane Doe , Disc 2: The boneyard ; Terminal leave ; Call of silence ; Heart break , Disc 3: Forced entry ; Chained ; Black water ; Doppelgänger , Disc 4: The meat puzzle ; Witness ; Caught on tape ; Pop life , Disc 5: An eye for an eye ; Bikini wax ; conspiracy theory ; Red cell , Disc 6: Hometown hero , SWAK , Twilight.

Failure to launch (Paramount Pictures, 2006)
Tripp is a thirtysomething slacker, but that doesn't mean that he is ready to give up the many benefits of living at home with his mom and dad. His desperate parents have had enough though, and after years of gentle nudging they soon realize that it is going to take a concerted effort to get Tripp out so they can enjoy their twilight years in peace. Realizing that their only hope for riding themselves of their reluctant-to-leave son, Al and Sue hope that on the off-chance Tripp will meet the woman of his dreams, the two enlist the help of a beautiful and talented woman in providing the romantic incentive needed to finally get their son out of the family home.